Comparative Constitutionalism in Central Europe – Summary - Csink, Lóránt (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Constitutions are more than legal documents that regulate the structure of the state and the relationship between the state and individuals. They also manifest the tradition, identity and political customs of the respective country. Different histories form different values which provide different interpretations of the constitutional text. Despite the similarities of constitutional institutions, one may see that constitutions are rather various. To provide a general overview on the constitutionalism of Central European Post-Socialist countries, the volume first goes through the constitutional history of the examined states, then it analyses certain aspects of constitutional institutions. The last chapter aims to summarise the most basic findings of the previous chapters.KEYWORDS: Comparative constitutionalism, constitutional history, state structure.